ANALYSIS OF POSTOPERATIVE OUTCOMES OF DEGENERATIVE DISEASES OF THE LUMBOSACRAL JUNCTION - Byvaltsev,Vadim Anatol'evich (2018)
ABSTRACT Objective: The article presents an analysis of the clinical efficacy and causes of unsatisfactory outcomes of surgical treatment in patients with degenerative diseases of the lumbosacral junction of the spine. Methods: Patients were allocated to one of three groups, depending on the method of surgical intervention on the lumbosacral junction: 1) (n=352) - operated by the method of microsurgical discectomy; 2) (n=83) - operated with the use of artificial IVD prostheses; 3) (n = 183) - operated with the use of interbody fusion and posterior rigid stabilization. To investigate the causes of unsatisfactory outcomes, a correlation analysis was conducted of long-term clinical outcomes with preoperative instrumental parameters in the operated segment, surgical tactics used, and the development of complications. Results: It is determined that long-term “good” clinical outcomes are associated with individual preoperative parameters of the lumbosacral junction of the spine - linear displacement, sagittal angulation, height of the interbody space, degree of IVD degeneration by ADC. Conclusion: In degenerative diseases of the lumbosacral junction of the spine, the detailed analysis of long-term clinical outcomes enable the identification of the causes that affect the development of unsatisfactory outcomes, which are individual morphostructural changes in the lower lumbar segment: the amplitude of the segmental angle, the angle of the lumbar lordosis, the degree of linear displacement of the vertebrae, the height of the interbody space, and ADC. Complex clinical and instrumental analysis enabled us to determine possible surgical tactics. Level of Evidence II; Prognostic Studies— Investigating the Effect of a Patient Characteristic on the Disease Outcome.